2016
DOI: 10.1007/s10661-016-5353-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and risk assessment of selected organochlorine pesticides in Kyzyl Kairat village from Kazakhstan

Abstract: Concentrations of selected organochlorine pesticides (OCPs), i.e., 4,4'-dichlorodiphenyltrichloroethane (p,p'-DDT), its metabolites (p,p'-DDE, p,p'-DDD), and hexachlorocyclohexanes (HCHs), have been determined in 100 soil samples collected from a contaminated site centered around a former storehouse in the Kyzyl Kairat village, Almaty region, Kazakhstan, which constitutes an exemplary case example. The OCPs were observed in all analyzed soil samples, with predominance of α-HCH, p,p'-DDD, p,p'-DDE, and p,p'-DDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In summer, the non-detectable target compounds were γ-BHC, heptachlor, 4,4-DDE, and endrin aldehyde, which could possibly have been converted to α-BHC, heptachlor epoxide, DDD or methoxychlor, and endrin, respectively, under favorable environmental conditions such as lower pH values, temperatures, and redox reactions [ 61 , 62 ]. The high concentration of methoxychlor, an important raw material for the production of certain insecticides and herbicides, could be associated with its low conversion through photo-oxidation [ 61 , 63 , 64 ]. γ-BHC, dieldrin, and endosufan II were detected at very low concentrations in summer, suggesting possible degradation to α-BHC, Eldrin, and/or endosulfan suplhate, respectively, at MSN.…”
Section: Resultsmentioning
confidence: 99%
“…In summer, the non-detectable target compounds were γ-BHC, heptachlor, 4,4-DDE, and endrin aldehyde, which could possibly have been converted to α-BHC, heptachlor epoxide, DDD or methoxychlor, and endrin, respectively, under favorable environmental conditions such as lower pH values, temperatures, and redox reactions [ 61 , 62 ]. The high concentration of methoxychlor, an important raw material for the production of certain insecticides and herbicides, could be associated with its low conversion through photo-oxidation [ 61 , 63 , 64 ]. γ-BHC, dieldrin, and endosufan II were detected at very low concentrations in summer, suggesting possible degradation to α-BHC, Eldrin, and/or endosulfan suplhate, respectively, at MSN.…”
Section: Resultsmentioning
confidence: 99%
“…However, potentially toxic elements (arsenic and heavy metals) were assessed the most often [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Among organic compounds the studies often included polycyclic aromatic hydrocarbons (PAHs), [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ], petroleum hydrocarbons [ 22 , 26 , 27 ] and pesticides [ 3 , 11 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…HCH isomers and lindane were reportedly not manufactured in Kazakhstan, but likely included among imported pesticides and stockpiles. According to the Ministry of Agriculture, HCH was not used in the territory of Kazakhstan, however a recent study reported high concentrations of organochlorine pesticides, including residues of DDT and HCH, in soils around a former storage facility in eastern Kazakhstan (Sailaukhanuly et al, 2016). These results suggest at the very least that lindane has been used or accumulated in soils upstream.…”
Section: Regulatory Framework-pops Convention In Central Asiamentioning
confidence: 98%